Modulations of Hibiscus sabdariffa Extract on Ethanol Induced Hepatotoxicity - R. N. Ativie; A. A. Aigbiremolen; R. E. Ubom; V. O. Oseh; O. M. Odigie; J. C. Igweh (Archives of Current Research International, 2017)
Commonly known as “zobo”, Hibiscus sabdariffa has been used in different parts of the world for medicinal and nutritional purposes. This work studied its activity on the liver in its course of daily usage as a refreshing social drink. The methanol extract of the dried plant’s petals was prepared by a 96 hours cold maceration; following which an acute toxicity testing was found to be safe (LD50 > 5000 mg/kg). The extract was evaporated with Soxhlet evaporator. It was later reconstituted and orally administered at graded doses (20, 40, 80 and 160 mg/kg) via orogastric cannula to 30 albino rats (180-200 g; n = 6), with one group serving as control. This administration occurred after ethanol was locally used to induce hepatotoxicity in rats. After six weeks of drug administration, the rats were sacrificed by cervical dislocation and blood samples were collected for assays. The results showed a significant dose-dependent decrease in serum alanine aminotransferase, aspartate aminotransferase and Bilirubin at a dose 160 mg/kg. Thus, it is suggested that the use of extracts of Hibiscus sabdariffa for a long period of time should be encouraged.